Consequences Of Defense For The Parties In The Agreement To Surrender The Position Of General Chairman Of The Sukabumi Young Man Association Football Club 1928 (Study Decision Number 38/Pdt.G/2021/Pn.Skb) - Sunardi, Sunardi; Rokhim, Abdul; Rizka Maulidina, Sonia (International Significance of Notary, 2024)
Abstract : Klup YMA 28 is a Klup in Sukabumi, but in advancing football the management borrowed money from a 3rd party and caused a lawsuit in court which was considered by one of the parties to be in default in handing over his position. This research is nurmative research and research results of legal consequences for parties who violate the agreement (default) handing over the position of general chairman of Yma Sukabumi Football Club 1928 based on decision number 38/Pdt.G/2021/Pn.Skb according to civil lawThe results of the author's analysis show that the agreement is legally valid, but does not meet the requirements for the validity of an agreement, namely the dictum regarding what was agreed in the Agreement Letter Number: 20190049/SMI/SP/X/2019 made by the Plaintiff and Defendant is something that is not clear, Is there an agreement regarding coaching money (article 3) or the issue of the position of general chairman (article 4) and in the agreement there is no article that explains the specific rights and obligations that must be fulfilled by the parties. However, the Mandate Letter Number: 20190058/MAN/SURMAN/X/2019 does not explain the object of the agreement in the mandate letter, what will be given by the Defendant as the first party and what will be obtained by the Plaintiff as the second party or not. explain the rights and obligations of the parties in the mandate letter. Apart from that, the Panel of Judges assessed that the agreement and mandate letter made between the Plaintiff and the Defendant did not have a clear or vague agreement object, so that the agreement and mandate letter did not fulfill the third requirement of Article 1320 of the Civil Code. So the lawsuit is deemed not to meet the requirements for the validity of an agreement so that the legal consequence is that the agreement is invalid and the defendant is obliged to return the construction money to the plaintiff because it is borrowed money. And the binding force of the agreement to hand over the position of general chairman of the YMA Sukabumi Football Club 1928 is linked to the principle of freedom of contract. with the management of the YMA football club in coaching and are free to contract with anyone, however, in making the terms of an agreement so that it is binding, the parties must be guided by article 1320 of the Civil Code and there are clauses regarding default and fulfillment of achievements and resolving disputes. So that if a dispute or dispute occurs, a judge can provide a sense of justice for those who desire it.Keywords, Agreement, Default, Court Decision,